Interproximal bone in maxillary anterior teeth in subjects with Class III facial deformity: Are there options for segmental maxillary osteotomy in "surgery first"?. Issue 2 (February 2019) - Brito, L.; Olate, S.; Villa, J.; Navarro, P.; Haidar, Z.S.; de Moraes, M.
Abstract: Our aim was to give a morphometric description of the interproximal bone between the anterior maxillary teeth of subjects with class III facial deformity, who were candidates for segmented Le Fort I osteotomy. We measured the width of the interproximal bone from the upper right canine to the upper left canine in cone-beam computed tomographic images of 35 subjects, and identified five interproximal areas of measurement. The lower and upper measurements were established 5 mm and 10 mm from the cervical crest of the interproximal bone. A paired samples t test and Pearson's correlation coefficient were applied and probabilities of less than 0.05 were accepted as significant. In all the scans of interproximal bone, the apical zone was significantly wider than the inferior zone (p < 0.001 ). The area between the central incisors was the widest, with a mean (SD) of 2.42 (0.68) mm in the lower, and 4.27 (0.99) mm in the upper, region followed by the space between the canines and lateral incisors. The minimum interproximal spaces in the lowest area were between 1.1 and 1.5 mm, which suggested the potential for damage to the teeth during segmental osteotomy. The interproximal spaces were at potential risk of dental and periodontal injuries, and the area between the central incisors seemed to be most suited to interproximal osteotomies in "surgery first".